Tort law - Markesinis, B. S. (Clarendon, 1996)
Originally published under the names Dias and Markesinis, this is a guide to torts for students and practitioners. The authors explain why and how this branch of the law is so intellectually untidy, and they show how it has suffered as a result of conflicting judicial, academic and legislative attempts to shape and rationalize it. For this edition, the text has been substantially rewritten by Simon Deakin and Basil Markesinis. The treatment of the subject is now far more detailed and the sections on product liability, damages, medical liability, and privacy has been expanded.